Government, Society, School, Parents and Students Factors as Correlates of Academic Dishonesty among Students in Oyo State, Nigeria. (2020)
The purpose of this study was to determine the relationship, composite and relative contribution of independent variables to academic dishonesty in Oyo state, Nigeria. The study was a descriptive research design of correlational type. The sample of the study consisted of 541educational stakeholders and society members, parents and students alike that were purposefully selected from Oyo state, Nigeria. The sample was selected using stratified random sampling techniques among strata of the respondents. The instruments used for data collection is an Academic Dishonesty scale which is divided into seven sections. The first section is demographic information about the participants, section ‚A‛ to ‚F‛ measures the independent variable and section ‚G‛ measures the dependent variable indices of Academic dishonesty variable. The roles of government, society, school, parents and students’ roles in academic dishonesty respectively have reliability coefficients of 0.75, 0.72, 0.81, 0.67, 0.84 and 0.79respectively. Three research questions were generated in the course of the study. Pearson Product Moment Correlation and Multiple Regression statistical methods were used for data analysis. Results indicated that significant relationship existed between each of the independent variables on academic dishonesty, also, significant joint relationship existed among these variables and all the independent variables were potent predictors of academic dishonesty in Oyo state, Nigeria. Among others, it was recommended that more studies on academic dishonesty are needed in Nigeria so that efforts at improving the standard of education in Nigeria could be enhanced.